The Power Struggle between The Colonizer and The Colonized through Fanonism in July’s People by Nadine Gordimer - Kızıltaş, Şahin; UYSAL, M. Başak (Journal of History Culture and Art Research, 2015)
The Power Struggle between The Colonizer and The Colonized through Fanonism in July’s People by Nadine Gordimer Abstract Frantz Fanon is an outstanding figure whose theories are attached great importance in post-colonial studies by researchers and literary critics. His theories particularly on violence and national consciousness have been discussed for many years, even today. The colonizers have charged him with legitimating violence and for them he is responsible for the bloody picture in the colonial world. On the other hand, the colonized people have regarded him as the prophet of the Third World raising national consciousness of the oppressed and the excluded. As a white novelist in South Africa during and after apartheid regime, Nadine Gordimer takes an important place in post-colonial studies due to her attention on political and racial issues. Among her masterpieces, written in 1981 after Soweto Uprising and banned by the white regime, July’s People comes to the forefront. It is the story of a white family, The Smales, fleeing from Johannesburg to the small village of their black servant, July, during the civil war in South Africa. In this requisite travel, the roles of white family and their black servant substitute. The black people become the protectors of the white family who have been the master of the black in the city. However, the white family does not seem to be eager to leave their power, dominion and superiority even in rural area among black society.